Effect of plasticizer type on tensile property and in vitro indomethacin release of thin films based on low-methoxyl pectin - Pensak Jantrawut (2018)
© 2017 by the authors. This study developed the interests of low-methoxyl pectin (LMP) together with plasticizers for the preparation of elastic thin films. The effect of different plasticizer types (glycerol: Gly; sorbitol: Sor propylene glycol: PG; and polyethylene glycol 300: PEG 300) and concentrations (20-40% w/w) on mechanical and thermal properties of LMP films as well as on in vitro release of indomethacin were evaluated. Without any plasticizer, a brittle LMP film with low tensile strength and % elongation at break was obtained. Addition of plasticizers from 20% to 40% caused reduction in the tensile strength and Young's modulus values, whereas percent elongation was increased. Forty percent Gly-plasticized and PG-plasticized films were selected to deliver indomethacin in comparison with non-plasticized film. No significant difference in indomethacin release profiles was displayed between the films. The analysis of indomethacin release model indicated that more than one drug release mechanism from the film formulation was involved and possibly the combination of both diffusion and erosion. Even though indomethacin incorporated in non-plasticized film showed similar release profile, Gly or PG should be added to enhanced film flexibility and decrease film brittleness.